Kaedah Pengajaran Rasulullah SAW: Analisis Modul Penghayatan Hadis 40 Imam Nawawi - Muhammad Hisyamuddin Kamarudin; Amran Abdul Halim; Nidzamuddin Zakaria (Global Academic Excellence (M) Sdn Bhd (GAE), 2026)
Tier 3- Indexed by MyCite